2006
DOI: 10.1111/j.1095-8339.2006.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

The genus Cochlearia L. (Brassicaceae) in the Eastern Carpathians and adjacent area

Abstract: Most European scurvy grasses (including those of the Carpathian Mountains) belong to the nominate section Cochlearia . We analyse the status of two East Carpathian (Romanian) Cochlearia populations by comparing them with the two native species from the Western Carpathians, the diploid Cochlearia pyrenaica (2 n = 2 x = 12; 2C = 0.78 pg) and hexaploid C. tatrae (2 n = 6 x = 42; 2C = 2.09 pg). Using karyological methods and flow cytometry, differences between these taxa were detected. Because of differences in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…Yet, in the SplitsTree network, the two C. bavarica samples are grouped closely together, both connected to a C. pyrenaica sample from Baden-Württemberg (Hohenlohe). This result supports the idea of a single ancient origin followed by genetic differentiation over geographic distances and later disruption of the continuous distribution into two refuge distribution areas as suggested by Koch (2002) (Bajer 1951;Koch et al 1996;Koch et al 1998;Koch et al 2003;Kochjarová et al 2006). The nuclear genomes indicate a shared evolutionary history and group all them into a monophyletic clade (Appendix 1-figure 12).…”
Section: Cochlearia Bavarica (2n=6x=36)supporting
confidence: 87%
“…Yet, in the SplitsTree network, the two C. bavarica samples are grouped closely together, both connected to a C. pyrenaica sample from Baden-Württemberg (Hohenlohe). This result supports the idea of a single ancient origin followed by genetic differentiation over geographic distances and later disruption of the continuous distribution into two refuge distribution areas as suggested by Koch (2002) (Bajer 1951;Koch et al 1996;Koch et al 1998;Koch et al 2003;Kochjarová et al 2006). The nuclear genomes indicate a shared evolutionary history and group all them into a monophyletic clade (Appendix 1-figure 12).…”
Section: Cochlearia Bavarica (2n=6x=36)supporting
confidence: 87%
“…In particular, the confusing taxonomic status of a Cochleria population in Ukraine, treated in some previous studies (including the Red Data Book in Ukraine Sobko 1996), as C. polonica and in some as C. pyrenaica, was also verified based on examinations of genetic variation. It was shown that the population represented the diploid C. pyrenaica and not C. polonica, which confirmed the status of C. polonica as a taxon endemic to Southern Poland only (Cielak and Ronikier 2006;Cielak et al 2007b;Kochjarová et al 2006).…”
Section: Introductionsupporting
confidence: 58%
“…Its natural distribution range in southern Poland was restricted to the upper part of the Biała river near Olkusz (Wyżyna Śląsko‐Krakowska upland). In addition, there has been a long‐lasting controversy about the taxonomic status of an isolated population of Cochlearia in Ukraine, treated by various authors as either C. polonica or C. pyrenaica (for example, Pobedimova, 1970; Vogt, 1985); however, with the use of genetic markers and chromosome numbers, it has been demonstrated that this population has close affinities to C. pyrenaica (Kochjarová et al ., 2006; Cieślak et al ., 2007). This confirms the unique status of C. polonica as a critically endangered, strictly endemic species of southern Poland, with only one stable population known.…”
Section: Methodsmentioning
confidence: 99%